Development of Teaching Materials for a New Accounting Paradigm: From Concepts to Green Accounting Types - Nicholas Renaldo; Andi Andi; Novita Yulia Putri; Fitri Yani (International Conference on Business Management and Accounting, 2023)
A new accounting paradigm known as Green Accounting emerged as a response to the environmental challenges faced by the world today. This study aims to present the development of teaching materials regarding Green Accounting. This study uses a qualitative approach and literature study to develop teaching materials. Based on the results of the development of green accounting teaching materials, the conclusion of this study is that the paradigm of accounting has changed from conventional accounting to green accounting. From the development of this teaching material can be seen introduction, definition, paradigm shift, related regulations, developments, challenges, and types of green accounting. This research is expected to improve the quality of academic teaching materials, especially in multiparadigm accounting and green accounting courses. This research is also expected to be developed for subsequent teaching materials such as why, how, and objectives of green accounting, green gross domestic product, environmental accounting, social accounting, space accounting, and others.